Lorsque la carte crée le territoire : l’invention de l’Alsace-Lorraine - Benoit Vaillot (M@ppemonde)
The map of the General Government of Alsace (Das Gebiet des General-Gouvernements im Elsass) produced by the Geographical and Statistical Division of the Prussian General Staff in September 1870 largely prefigured the territory that would form “Alsace-Lorraine” (Elsaß-Lothringen) between 1871 and 1918. This territory, which France ceded to the German Empire at the end of the war, was still only a paper abstraction before a demarcation commission made it tangible. In the process of their demarcation operations, the commissioners surveyed, mapped and described the new Franco-German border and, at the same time, the limits of the annexed territory. Based on the commission’s archives, this article proposes to reconstruct the role played by maps in the invention of Alsace-Lorraine during the 1870s.